THE ANALYSIS OF LEARNING MOTIVATION ON COLLEGE STUDENT OF ELEMENTARY SCHOOL TEACHER EDUCATION COURSES IN THE SCIENCE BASIC CONCEPT - Mohammad Taufiq; Herawati Susilo; Mimien Henie Irawati Al Muhdhar; Murni Saptasari (JURNAL PENA SAINS, 2019)
Motivation in learning will influence the student to be a success. Four aspects that became part of the motivation is the fundamental aspects of attention, relevance, confidence, and satisfaction. The purpose of this research is to know the extent to which students ' motivation of elementary school teacher education on the basic concept of subject science. The method used is descriptive quantitative survey method; in this case, use the question form of student motivation. This research was carried out in April 2016. The subject of research is the 234 students distributed in University of Nahdlatul Ulama Surabaya and the State University of Surabaya. The results showed that students ' learning motivation of elementary school teacher education in aspects of attention, relevance, and satisfaction are on the category quite nicely, while confidence is at a type less well this defines the that required increased efforts of student learning motivation on the subject the basic concept of science.